Vitamin D - Beyond Bones: Its Relationship to Obesity, Metabolic Syndrome, and Diabetes - Wongvibulsin, Shannon; Vazirani, Sondra; Li, Zhaoping; Heber, David (Journal of Nutritional Therapeutics, 2014)
While vitamin D has long been known as an essential nutrient for the prevention of bone disorders, vitamin D deficiency has recently been linked to a number of chronic disease states. This review analyzes the epidemiological, clinical, and mechanistic data concerning the relationship between vitamin D status and obesity, metabolic syndrome (MetS), and diabetes. The increased understanding of the role of vitamin D has promoted researchers to study vitamin D as a potential target for the prevention and treatment of multiple chronic diseases.